Congenital human herpesvirus 6 infection in a full-term newborn: literature review and case report - A. L. Karpova; A. V. Mostovoi; A. A. Baranov; L. A. Anikeeva; E. V. Klubnichkina; A. L. Zaplatnikov; L. N. Karpov (Акушерство, гинекология и репродукция, 2020)
Neonatal human herpesvirus type 6 (HHV-6) infection is an extremely rare disease. HHV-6 is a unique virus because it is able to integrate into human chromosomes to be further transmitted vertically from parent to offspring. In humans, HHV-6 is associated with a wide range of clinical manifestations and, in children, may present as roseola infantum, febrile seizures, aphthous stomatitis, mononucleosis-like syndrome, or fever of unknown origin. This article reports a rare case of congenital HHV-6 infection in a newborn. To date, both Russian and international publications provide very limited descriptions of such cases, which, in our opinion, reflects a significant knowledge gap among neonatologists regarding this condition. We discuss the clinical forms of HHV-6 infection in neonates, rare case presentations, and current approaches to diagnosis and treatment.